Ethics in E-Commerce: The Self-Regulation Approach - López Jiménez, David; Dittmar, Eduardo Carlos; Vargas Portillo, Jenny Patricia (Law, State and Telecommunications Review, 2025)
[Purpose] To explore the application and effectiveness of self-regulation tools in the e-commerce sector, focusing on their role in enhancing consumer protection in the digital world. The research seeks to evaluate how self-regulation mechanisms, such as codes of conduct, complement existing legal frameworks to protect consumer rights and build trust in online transactions. [Methodology/approach/design] The study employs a comprehensive analysis of self-regulation concepts, examining their influence in various digital environments. It investigates the necessary conditions for effective self-regulation systems and the potential legal characteristics of these mechanisms. The research draws on theoretical and practical insights, comparing self-regulation tools with traditional contractual frameworks like adhesion contracts. [Findings] The analysis reveals that self-regulation tools, particularly codes of conduct, play a significant role in filling gaps left by existing legal regulations. These tools enhance consumer protection by setting higher standards than those mandated by law. The study highlights the functional similarity between self-regulation instruments and adhesion contracts, noting that while they lack the coercive power of legal norms, they effectively standardize practices and build consumer trust. [Practical implications] The findings suggest that businesses should adopt self-regulation tools to strengthen consumer trust and compliance with ethical standards. These tools can lead to improved consumer experiences and potentially reduce legal disputes by addressing issues that legal regulations may not cover comprehensively. The research underscores the need for businesses to publicize their adherence to these codes to maximize their impact on consumer trust and corporate reputation. [Originality/value] This paper provides a detailed examination of self-regulation tools in e-commerce, offering new insights into their legal nature and practical applications. It is valuable for policymakers, e-commerce businesses, and consumer protection agencies interested in understanding how voluntary compliance mechanisms can enhance legal frameworks and improve consumer protection in the digital marketplace.